2021
DOI: 10.1177/03611981211013349
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Express Train Preference of Urban Railway Passengers Based on Extreme Gradient Boosting (XGBoost) using Smart Card Data

Abstract: As the share of public transport increases, the express strategy of the urban railway is regarded as one of the solutions that allow the public transportation system to operate efficiently. It is crucial to express the urban railway’s express strategy to balance a passenger load between the two types of trains, that is, local and express trains. This research aims to estimate passengers’ preference between local and express trains based on a machine learning technique. Extreme gradient boosting (XGBoost) is tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Studies on urban or suburban express railway services like GTX have found that the properties of express railways such as mobility (3) and punctuality (4) have a great influence on the mode choice process. In addition, the possibility of using the suburban express rail is also increased through reducing the out-vehicle time (5) by improving accessibility or strengthening the linkage of modes and enhancing convenience by reducing congestion (6,7) in the vehicle and similar results are obtained from studies on Gyeong-in Line and Line 9 (8)(9)(10) in the metropolitan area of Seoul based on transportation card data. Although these studies could provide meaningful insights about properties of express rail or suburban rail services in mode choice process, diverse travel contexts which might affect the utility of using the express railway services tend to be ignored.…”
supporting
confidence: 58%
“…Studies on urban or suburban express railway services like GTX have found that the properties of express railways such as mobility (3) and punctuality (4) have a great influence on the mode choice process. In addition, the possibility of using the suburban express rail is also increased through reducing the out-vehicle time (5) by improving accessibility or strengthening the linkage of modes and enhancing convenience by reducing congestion (6,7) in the vehicle and similar results are obtained from studies on Gyeong-in Line and Line 9 (8)(9)(10) in the metropolitan area of Seoul based on transportation card data. Although these studies could provide meaningful insights about properties of express rail or suburban rail services in mode choice process, diverse travel contexts which might affect the utility of using the express railway services tend to be ignored.…”
supporting
confidence: 58%
“…This section will briefly summarize the gradient boosting regression tree architecture and the XGBoost model structure as described in detail in [31][32][33][34][35]. GBRT is an advanced decision tree model that uses the concept of boosting, i.e., combining weak learners with other, iteratively formed, weak learners (decision trees) to form a strong predictor.…”
Section: Gradient Boosting Tree Architecturementioning
confidence: 99%
“…This technique has been used extensively in traffic safety studies, including crash injury prediction, to better interpret risk factors ( 45 , 46 ). In recent years, SHAP has also been used to estimate and interpret transportation mode preferences from a variety of data sources, including smart cards and travel surveys ( 47 , 48 ).…”
Section: Literature Reviewmentioning
confidence: 99%